ANALYSIS OF THE EFFECT OF ASSETS GROWTH AND CAPITAL STRUCTURE ON PROFITABILITY WITH MANAGEMENT OWNERSHIP AS A MODERATING VARIABLE IN REAL ESTATE AND PROPERTY COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN 2011-2013 - Silalahi, Harlen (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the study was to analyze the influence of asset growth and capital structure on profitability with management ownership as moderating variable at real estate and property companies listed in the Indonesia Stock Exchange, in the period of 2011-2013. The samples consisted of 38 companies with 114 analysis units, taken by using saturated or census sampling technique when the population was used as the samples. The data were gathered by conducting documentary study; secondary data were financial statement and annual report, which were publicized through website.idx.co.id, stock price, and composite stock price index. The gathered data were analyzed by using multiple linear regression analysis and residual analysis for moderating variable. The result of the research showed that, simultaneously and partially, asset growth and capital structure had significant influence on profitability at real estate and property companies listed in the Indonesia Stock Exchange, in the period of 2011-2013. It was also found that management ownership was able to moderate (enforce) the correlation of asset growth and capital structure with profitability at real estate and property companies listed in the Indonesia Stock Exchange, in the period of 2011-2013.